Kallistatin limits abdominal aortic aneurysm by attenuating generation of reactive oxygen species and apoptosis - Krishna, Smriti Murali; Li, Jiaze; Wang, Yutang; Moran, Corey S.; Trollope, Alexandra; Huynh, Pacific; Jose, Roby; Biros, Erik; Ma, Jianxing; Golledge, Jonathan (Scientific reports, 2021)
Inflammation, vascular smooth muscle cell apoptosis and oxidative stress are believed to play important roles in abdominal aortic aneurysm (AAA) pathogenesis. Human kallistatin (KAL; gene SERPINA4 ) is a serine proteinase inhibitor previously shown to inhibit inflammation, apoptosis and oxidative stress. The aim of this study was to investigate the role of KAL in AAA through studies in experimental mouse models and patients. Serum KAL concentration was negatively associated with the diagnosis and growth of human AAA. Transgenic overexpression of the human KAL gene ( KS-Tg ) or administration of recombinant human KAL (rhKAL) inhibited AAA in the calcium phosphate (CaPO 4 ) and subcutaneous angiotensin II (AngII) infusion mouse models. Upregulation of KAL in both models resulted in reduction in the severity of aortic elastin degradation, reduced markers of oxidative stress and less vascular smooth muscle apoptosis within the aorta. Administration of rhKAL to vascular smooth muscle cells incubated in the presence of AngII or in human AAA thrombus-conditioned media reduced apoptosis and downregulated markers of oxidative stress. These effects of KAL were associated with upregulation of Sirtuin 1 activity within the aortas of both KS-Tg mice and rodents receiving rhKAL. These results suggest KAL-Sirtuin 1 signalling limits aortic wall remodelling and aneurysm development through reductions in oxidative stress and vascular smooth muscle cell apoptosis. Upregulating KAL may be a novel therapeutic strategy for AAA.